Flame-acoustics interaction for flames propagating from the open to the closed end of a channel: effects of heat losses and the Lewis number - Jiménez, Carmen; Kurdyumov, Vadim (Elsevier, 2022)
In this paper we present a numerical study of the impact of heat losses and the differential diffusion effect on the flame-acoustics interaction, for flames propagating from the open to the closed end of a planar channel. It has been recently demonstrated that for Le=1 symmetric and non-symmetric flames produce different acoustic responses in adiabatic channels. The results of the present study show that the interaction of the flame with the acoustic field is significantly influenced by heat losses and the Lewis number through a change in the shape of the flame: increasing the heat losses tends to make the flames symmetric and low Lewis numbers result in non-symmetric flames.
Keywords: Premixed flames; Flame instabilities; Thermo-acoustic instabilities; Non-symmetric flames; Heat-losses